153k views
1 vote
Can you help me with this math problem? Im having a hard time with it, if you can explain it too that would help a lot. attachment below

Can you help me with this math problem? Im having a hard time with it, if you can-example-1

1 Answer

1 vote

Answer:


3^(-3)\cdot \:\:8^(-3)=(1)/(24^3)

Thus, the equivalent expression is:
(1)/(24^3)

Explanation:

Given the expression


3^(-3)\cdot 8^(-3)


\mathrm{Apply\:exponent\:rule}:\quad \:a^(-b)=(1)/(a^b)


=8^(-3)\cdot (1)/(3^3)


\mathrm{Apply\:exponent\:rule}:\quad \:a^(-b)=(1)/(a^b)


=(1)/(3^3)\cdot (1)/(8^3)


\mathrm{Multiply\:fractions}:\quad (a)/(b)\cdot (c)/(d)=(a\:\cdot \:c)/(b\:\cdot \:d)


=(1\cdot \:1)/(3^3\cdot \:8^3)


=(1)/(24^3)

Thus,


3^(-3)\cdot \:\:8^(-3)=(1)/(24^3)

Thus, the equivalent expression is:
(1)/(24^3)

User Adiant
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.